The role of green supply chain management and green innovation in the effect of corporate social responsibility on firm performance - Maya Novitasari; Dian Agustia (Gestão & Produção, 2022)
Abstract: The application of social performance as a material for transparency of environmental commitments that drive company management on company performance is required in the firms. The purpose of this study was to look into the environmental implications of the firms, specifically the role of green supply chain management and green innovation as intervening variables between the effect of corporate social responsibility on firm performance and the effect of corporate social responsibility on firm performance. This was quantitative research. PROPER companies listed on the Indonesia Stock Exchange from 2015 to 2019 comprised the study's population. Research data was obtained from the Indonesia Stock Exchange. The sample for this study was 211 companies' annual reports and financial statements, which were obtained through a purposive sampling method. STATA was used to test the data in this study. The results of the study revealed that green supply chain management mediated the effect of corporate social responsibility on firm performance, green innovation did not mediate the effect of corporate social responsibility on firm performance, green supply chain management mediated the effect of corporate social responsibility on green innovation, and green innovation did not mediate the effect of green supply chain management on firm performance.